Design and optimization of cranberry extract loaded bile salt augmented liposomes for targeting of MCP-1/STAT3/VEGF signaling pathway in DMN-intoxicated liver in rats - Sara M. Soliman; Shaimaa Mosallam; Mohamed A. Mamdouh; Mohammed Abdalla Hussein; Shady M. Abd El-Halim (Taylor & Francis Group, 2022)
Cranberry extract (CBE) is a major source of the antioxidant polyphenolics but suffers from limited bioavailability. The goal of this research was to encapsulate the nutraceutical (CBE), into bile salt augmented liposomes (BSALs) as a promising oral delivery system to potentiate its hepatoprotective impact against dimethylnitrosamine (DMN) induced liver injury in rats. The inclusion of bile salt in the liposomal structure can enhance their stability within the gastrointestinal tract and promote CBE permeability. CBE loaded BSALs formulations were fabricated utilizing a (23) factorial design to explore the impact of phospholipid type (X1), phospholipid amount (X2), and sodium glycocholate (SGC) amount (X3) on BSALs properties, namely; entrapment efficiency percent, (EE%); vesicle size, (VS); polydispersity index; (PDI); zeta potential, (ZP); and release efficiency percent, (RE%). The optimum formulation (F1) exhibited spherical vesicles with EE% of 71.27 ± 0.32%, VS; 148.60 ± 6.46 nm, PDI; 0.38 ± 0.02, ZP; −18.27 ± 0.67 mV and RE%; 61.96 ± 1.07%. Compared to CBE solution, F1 had attenuated DMN-induced hepatic injury, as evidenced by the significant decrease in serum level of ALT, AST, ALP, MDA, and elevation of GSH level, as well as SOD and GPX activities. Furthermore, F1 exhibited an anti-inflammatory character by suppressing TNF-α, MCP-1, and IL-6, as well as downregulation of VEGF-C, STAT-3, and IFN-γ mRNA levels. This study verified that when CBE was integrated into BSALs, F1, its hepatoprotective effect was significantly potentiated to protect the liver against DMN-induced damage. Therefore, F1 could be deliberated as an antioxidant, antiproliferative, and antifibrotic therapy to slow down the progression of hepatic damage.